PERBEDAAN KEPERCAYAAN DIRI SISWA YANG AKTIF ORGANISASI DENGAN SISWA YANG TIDAK AKTIF ORGANISASI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the picture of the level of confidence of students who are active organizations, to know the picture level of confidence of students who are not active organizations and to know the differences of confidence of students who are active organizations with students who are not active organizations. Hypothesis in this research is: There is difference of confidence between student active organization with student that not active organization. Population in this research is all student in class XI MIA SMAN 5 Pekanbaru. The sampling technique used in this study is saturated sampling, which is the technique of determining the sample when all members of the population are used as a sample. This study uses an instrument of confidence questionnaire. Based on the T-Test Independent Sample output, the value of sig. (2-tailed) or p-value of 0.00 is 0.05 (0.00 <0.05), it can be concluded accepted, Significant self-confidence between an active student organization with an inactive student organization. Where the confidence of active students of the organization is higher than the students' self-esteem inactive.Keywords: Self Confidence, Active Students Organization, Students Not Active Organization